PENGARUH PERENCANAAN STRATEGI DAN KOMPENSASI TERHADAP LEARNING AND GROWTH PADA PERGURUAN PENDIDIKAN ADVENT BANDUNG - Moody H. Manalu; Junita Manurung (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2021)
Each educational institution will provide the best in the learning process so that the school can be recognized for its quality based on the results of quality graduates by increasing the abilities and expertise (learning and growth) of educators. This study intends to see the effect of strategic planning and compensation on learning and growth. The population in this study were all employees who worked in Bandung Adventist educational institutions and as samples were teaching staff or teachers who were determined based on incidental samples. The findings obtained by statistical processing of SPSS 24 are that there is a positive and significant influence between strategic planning on learning and growth, as well as a positive influence between compensation on learning and growth. Simultaneously, there was a positive and significant influence between strategic planning and compensation on learning and growth